ANALYSIS OF THE GREEN ECONOMY SUSTAINABILITY STATUS IN INDONESIA USING MULTIDIMENSIONAL SCALING - Setyowati, Endah; Rahmawati, Anisa (Universitas Mataram, 2025)
This current study aims to investigate the sustainability of the Green Economy Index assessment in Indonesia. The green economy is an economic model that carries out economic activities while taking into account environmental sustainability and social welfare. The multidimensional scaling through the Rapid Appraisal for Green Economy Index (Rap-GEI) ordination technique was employed in this study. Rap-GEI is a technique for assessing the sustainability of the green economy in Indonesia according to a number of attributes that are easy to assess multidimensionally. The results of the current study show that the sustainability status of the GEI assessment is less sustainable (45.47%) for the environmental dimension, quite sustainable (56.02%) for the economic dimension, and quite sustainable (55.30%) for the social dimension. The most sensitive attributes that require improvement are managed waste and share of renewable energy (environmental dimension), agricultural productivity and industrial sector labor productivity (economic dimension), as well as poverty rate and life expectancy (social dimension). In general, the results show that two of the three dimensions, namely economic and social, have a fairly good rating, but the environmental dimension still shows a poor rating and needs to be improved.